Postive criminological forecast as a material contition for parole in Polish penal law - Niewiadomska-Krawczyk, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
This article refers to one of the most important institution in Polish Penal Code which is early conditional release as a part of probation. It is focused on the material circumstance of that institution which is positive criminological forecast. The aim of this article is to describe all the elements that have an influence on the criminological forecast and to decide if all of them are needed and if there is a chance to change the regulation to simplify them.
Keywords: przedterminowe warunkowe zwolnienie; kurator; pozytywna prognoza kryminologiczna; polski kodeks karny; stan prawny